Association of the COMT Val108/158Met genotype with professional career and education: The Val-allele is more frequent in managers and in enterprising occupations. (15th January 2018) - Kurrikoff, Triin; Kaarma, Katrin; Tooding, Liina-Mai; Vaht, Mariliis; Tulviste, Tiia; Veidebaum, Toomas; Harro, Jaanus
Abstract: Catechol- O -methyl transferase (COMT) is a key player in neurotransmission by catecholamines, and the functional COMT Val108/158Met polymorphism is strongly related to prefrontal reactivity and to dopamine levels. As dopamine is a critically important neurotransmitter in cognition, emotion and motivation, we addressed the potential impact of this genotype on life course by examining its association with being in enterprising professions. The parents ( n  = 1410) of the target subjects in the Estonian Children Personality Behaviour and Health Study reported their current occupation, and those classified as enterprising ( n  = 197; 18%) were compared with the remaining group. Additionally, the subjects self-classified themselves according to the International Standard Classification of Occupations and the group of managers (6.2%) was compared to other groups. We found that the COMT Val108/158Met Val/Val homozygotes were overrepresented among enterprising occupations and the Val-allele carriers among self-classified managers. While several measures associated with the Val/Val homozygosity were also associated with enterprising occupation, no simple path from the genotype to enterprising occupations emerged from structural equation models, suggesting that the COMT Val108/158Met genotype contributes to choices of profession via multiple interactive features. We also reproduced a previous finding that the COMT genotype is associated with educational attainment in a gender-dependent manner.